Pengembangan Kinerja Sumber Daya Manusia Disiplin dan Motivasi Kerja di Lingkungan SMK Angkasa Sepatan - Susanti, Santi (CV. Kalimasada Group, 2023)
Human performance, that is, human performance, includes the ability to think and physical strength, which are important elements that make up an organization. As a matter of fact, employee performance is still relatively low at SMK Angkasa, and the success of the organization is highly dependent on employee performance. This is reflected in inefficient working hours (not punctual) and lack of accountability for tasks. Motivate and train employees to solve employee performance issues that often arise in SMK Angkasa organizations and institutions. The purpose of this study is to clarify the effects of motivation and discipline in improving human resource performance in the work environment, and to clarify whether there are factors that hinder or support the improvement of human resource performance due to motivation and discipline in the work environment. . Respondents for this study were selected using objective sampling by distributing questionnaires to up to 88 employees. Based on research results, the R-squared (R2) value is only 0.242. This can be explained by the influence of work environment, discipline, and work motivation. Work environment, discipline, and work motivation all come together to have a significant positive impact on HR performance.